2007
DOI: 10.1111/j.1472-765x.2007.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methane and quantification of methanogenic archaea in faeces from young broiler chickens using real-time PCR

Abstract: Aims:  To detect the presence of methanogens in the faeces of broiler chicks during the first 2 weeks of age. Methods and Results:  Chicken faecal samples from 120 broiler chicks were incubated for methane gas formation and methanogenic archaea were analysed using real‐time PCR. The copy number of the order Methanobacteriales 16S rDNA gene in chicken faeces when the broilers were 3–12 days of age, litter and house flies collected in the bird house ranged from 4·19 to 5·51 log10 g−1 wet weight. The number of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
5
28
1
Order By: Relevance
“…A number of studies have quantified methanogens belonging to different phylogenetic groups with techniques such as dot blot hybridization and fluorescent in situ hybridization (27,38,57), as well as qPCR (19,41,42,(54)(55)(56). Quantitation in these studies has targeted 16S rRNA or the rRNA gene, but studies by Springer et al (49) and Bapteste et al (3) suggest that the mcrA gene demonstrates the same phylogenetic relationships as the 16S rRNA gene between organisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have quantified methanogens belonging to different phylogenetic groups with techniques such as dot blot hybridization and fluorescent in situ hybridization (27,38,57), as well as qPCR (19,41,42,(54)(55)(56). Quantitation in these studies has targeted 16S rRNA or the rRNA gene, but studies by Springer et al (49) and Bapteste et al (3) suggest that the mcrA gene demonstrates the same phylogenetic relationships as the 16S rRNA gene between organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative PCR (qPCR) is an alternate technique capable of determining the copy number of a particular gene present in the DNA extracted from an environmental sample. Only a few studies have used qPCR to quantitatively examine different clades within methanogen communities, and most of these studies have exclusively targeted the 16S rRNA gene (19,41,42,(54)(55)(56). Far fewer researchers have used qPCR to quantify methanogen clades by targeting the mcrA (21,34,45), and these studies were limited to only a few phylogenetic groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Archaea DNA provides about 1-2% of all caecal genetic information, whilst bacterial DNA provides about 95-97% (Qu et al 2008, Danzeisen et al 2011. However, according to Saengkerdsub et al (2007b) colonization of the methanogenic Archaea begins very early, within 3-5 days after hatching, and prior to that time, when the GIT is finally formed. Interestingly, some cellulolytic bacteria also found in the GITs of young chicks, such as Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…A psychrophilic anaerobic granular reactor was monitored with group-specific qPCR, which showed that the order Methanomicrobiales was dominant among methanogen groups [56]. The qPCR assay has also been employed in studies to investigate methanogen compositions in chicken ceca [57] and faeces [58], cattle rumen [59], and soil [60]. In conclusion, groupspecific primer and probe sets targeting methanogens have been successfully applied to quantitatively elucidate the microbial community structures in many different environments.…”
Section: Methanogensmentioning
confidence: 99%